(untitled) (International Journal of Physiotherapy, 2017)
Background: There are several manual therapy techniques for limited and painful knee flexion, but there are very few evidence about the effectiveness of Mulligan’s Mobilisation With Movement (MWM) in osteoarthritis of the knee. The objective of the study was to find the effect of MWM on pain and functional status in patients with osteoarthritis knee. Methods: 30 patients diagnosed with medial compartment tibiofemoral osteoarthritis of the knee were randomized into two groups ( experimental and control groups ) with 15 subjects in each group.The experimental group received medial glide MWM and medial rotation glide MWM in weight bearing and non-weight bearing positions after which the patients were asked to walk for a while. Conventional therapy in the form of shortwave diathermy (SWD), quadriceps strengthening and stretching of the calf and hamstrings was given to both the experimental and the control group. The intervention regimen lasted for seven days. Outcome measures were WOMAC score, VAS score and distance walked in 6-minute walk test. Result: The study showed significant improvement in VAS (p<0.05 in control group, p<0.001 in experimental group ), WOMAC scale(p<0.05 in control group, p<0.001 in experimental group) and distance walked in 6 minutes(p<0.05 in control group, p<0.001 in experimental group) in both the groups, but all these improvements were highly significant in experimental group ( p< 0.001 ) than those in the control group. Conclusion: Mulligan’s MWM is significantly effective in relieving pain and improving functional status in osteoarthritis of the knee.